(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: The coronavirus disease 2019 (COVID-19) pandemic exposed significant vulnerabilities in public health systems globally, particularly in low and middle-income countries like Pakistan. In response, predictive modeling has emerged as a critical tool to guide proactive pandemic preparedness, optimize resource allocation, and strengthen risk financing mechanisms. This study aimed to develop and validate predictive models tailored to the Pakistani context and to support evidence-based decision-making for future health emergencies. Methods: A mixed-methods approach was employed, integrating epidemiological forecasting, healthcare capacity modeling, cost-effectiveness analysis, and risk financing simulations. Data was sourced from multiple national institutions including the National Institute of Health (NIH), Lady Health Workers (LHW) Program, SehatSahulat Program (SSP), and also from international databases such as WHO and World Bank. Compartmental SEIR models and machine learning algorithms were used for outbreak forecasting. Discrete-event simulation (DES) assessed the healthcare system readiness under varying outbreak intensities. Economic evaluation was conducted using a Markov model to compare interventions. Stakeholder engagement informed policy relevance and implementation pathways. Results: Epidemiological models demonstrated high accuracy in predicting dengue and SARS-CoV-2 outbreaks, with an average prediction error (MAE) of ±6.8%. Healthcare capacity analysis revealed significant shortages during severe scenarios: ICU beds fell short by 71%, ventilators by 75%, and medical staff by 58%. Targeted vaccination emerged as the most cost-effective intervention, yielding 2.3 million DALYs averted at 280 million, followed by mass testing. Risk financing simulations indicated that a hybrid mechanism combining contingency reserves and catastrophe bonds could reduce unmet funding needs by up to 82%. Qualitative feedback from policymakers confirmed strong support for predictive analytics; it also highlighted existing challenges related to data interoperability and lack of technical capacity. Conclusion: Predictive modeling offers a robust framework for enhancing pandemic preparedness and guiding risk financing decisions in Pakistan. By leveraging local data and global modeling techniques, this study provides actionable insights for improving healthcare resilience, optimizing resource use, and strengthening fiscal preparedness. Institutionalizing predictive analytics within national health planning is essential to make an effective transition from reactive crisis management to proactive; also data-informed strategies have capability of mitigating the impact of future pandemics.